FOSTERING COMPLIANCE WITH WOMEN’S RIGHTS IN THE INTER-AMERICAN SYSTEM - Cook, Rebecca (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 1998)
This article explores why the practice of states in the Americas has been slow to comply with the human rights of women since the adoption of the American Declaration of the Rights and Duties of Man in 1948. The article explains that since states tend to obey international law as a result of repeated interaction among transnational actors, a first step toward fostering compliance is to empower more actors concerned with women, particularly marginalized women, to participate in the process. A next step is to explore how the available forums at both the regional and international levels have been and could be used to apply human rights to the harms experienced by women. Consistent with this step, the article reviews the case law concerning women developed by the Inter-American Court of Human Rights, the Inter-American Commission on Human Rights and the international treaty bodies. A third step toward fostering compliance is to assess strategies of how best to internalize women’s rights into domestic laws, policies and practices. Pursuant to this step, the article identifies some of the key concluding observations in the country reports of treaty bodies, and notes that most states have yet to change their laws to comply with these observations. The article concludes by examining how sanctions and rewards, or a mixture of the two, could be used to improve compliance with the human rights of women in the future.